2021
DOI: 10.1149/1945-7111/abfe42
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Highly Sensitive Imprinted Electrochemical Sensor for the Detection of Hydrocortisone in Wastewater

Abstract: The existence of hydrocortisone in water resources is a serious threat to human health. However, the rapid and sensitive detection methods for hydrocortisone in wastewater are still lacking. Meanwhile, due to the weak redox activity of hydrocortisone, electrochemical technique cannot be used to detect hydrocortisone directly. Therefore, molecularly imprinted technique combined with prussian blue nanoparticles was synthesized for detecting HC indirectly in this work. We fabricated a novel and highly sensitive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For a miniature sensor device, it is possible to integrate fluidics capable of actuating the delivery of the redox probe liquid to the sensing site [41]. A convenient approach to circumvent the need for a fluidic delivery system is by embedding a redox probe within the MIP scaffold during the electropolymerization process [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…For a miniature sensor device, it is possible to integrate fluidics capable of actuating the delivery of the redox probe liquid to the sensing site [41]. A convenient approach to circumvent the need for a fluidic delivery system is by embedding a redox probe within the MIP scaffold during the electropolymerization process [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the discharge of industrial sewage is considered to be one of the main sources of estrogen pollutant in the aquatic environment. 3,4 Among these, 17β-estradiol (E2), as one type of endocrine-disrupting chemical (EDC), has been detected in environment from different countries such as the United States, Germany, Italy, Brazil and China. [5][6][7] Therefore, the pollution of E2 in water environment has become a global pollution problem.…”
mentioning
confidence: 99%
“…Our previous research has also reported a sensitive imprinted electrochemical sensor for the detection of HC with much low LOD of 0.006 nM. 37 However, DXM and HC were usually co-existed in aquatic matrices. Due to the weak electro-activity and similar structure of them, it remains a challenge to achieve simultaneous determination of DXM and HC using electrochemical sensing analysis.…”
mentioning
confidence: 99%